A Modified Fast Approximated Power Iteration Subspace Tracking Method for Space-Time Adaptive Processing - Yang Zhiwei; He Shun; Liao Guisheng; Ouyang Shan (Journal of Electrical and Computer Engineering)
We propose a subspace-tracking-based space-time adaptive processing technique for airborne radar applications. By applying a modified approximated power iteration subspace tracing algorithm, the principal subspace in which the clutter-plus-interference reside is estimated. Therefore, the moving targets are detected by projecting the data on the minor subspace which is orthogonal to the principal subspace. The proposed approach overcomes the shortcomings of the existing methods and has satisfactory performance. Simulation results confirm that the performance improvement is achieved at very small secondary sample support, a feature that is particularly attractive for applications in heterogeneous environments.